MANIFESTASI KLINIS, DIAGNOSIS, DAN TATALAKSANA PUBERTAS PREKOKS - Anjely Doni Lasmi; Dhila Thasliyah; Ratih Fitriati (LPPMK STIKES Widyagama Husada, 2022)
The purpose of preparing this article is to understand more deeply about precocious puberty. The method used is a literature study from various sources, such as: 1) journal reviews, 2). scientific writing articles. Selection of journals and articles focused on precocious puberty, while reviews of articles and journals were carried out in the last 10 years from 2010-2020. Precocious puberty is defined as a condition in girls aged less than 8 years and boys aged less than 9 years who experience secondary sexual development, both physical and hormonal signs. Precocious puberty is classified into central precocious puberty and peripheral precocious puberty, both of which occur based on the etiology of the underlying condition or disease. Treatment can be given differently, in central precocious puberty can be given GnRH agonist therapy, and in peripheral precocious puberty can be treated to eliminate the source of sex steroids.